Dukungan dan Koping Keluarga dalam Motivasi Pengobatan Penderita Diabetes Melitus - Alva Cherry Mustamu; Sjarfan Sjarfan; Nur Hafni Hasim (Poltekkes Kemenkes Maluku, 2020)
Currently, people with diabetes melitus in Indonesia are increasing. The family plays an important role in meeting the care needs of individuals who need help due to illness and/ or disability. The need to move to family-centered care to improve well-being. This study aims to determine the relationship between family support and coping with the motivation of treating diabetes melitus in Sorong District Hospital. This research is a descriptive analytic study with cross-sectional design on 41 respondents who were collected using consecutive sampling techniques. Data collection using questionnaire sheets. The results of the calculation of the relationship between family coping and treatment motivation using the Spearman Rank correlation show the value of r=0.679 and p-value=0,000. The results of the calculation of the relationship between family support and treatment motivation using the Spearman Rank correlation show the value of r=0,912 and p-value=0,000. This research found that there is between coping and family support and treatment motivation. Factors that can increase motivation include family support and coping.